PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR INDUSTRI KIMIA - Linda Wati; Nugrahini Kusumawati; Efi Tajuroh A; Aris Trismayadi N (Universitas Bina Bangsa, 2021)
Accounting has an important role for companies through corporate financial reporting. Green accounting or also known as environmental accounting is an accounting system that studies accounts related to environmental costs. The purpose of this study is to determine the Environmental Performance and Environmental Disclosure individually (partially) or collectively (simultaneously) on the profitability of the chemical industry sub-sector companies listed on the Indonesia Stock Exchange for the period 2015-2019. This research uses quantitative methods with a descriptive approach. The population in this study were 13 chemical industry sub-sector companies listed on the Indonesia Stock Exchange for the period 2015-2019. Sampling in this study using a purposive sampling technique, namely as many as 6 companies. The results of the research on the effect of the application of Green Accounting on profitability obtained the value of Fcount> Ftable (2.274 > 2.04), then Ha is rejected, which means that environmental performance and environmental disclosure do not jointly affect profitability in chemical industry sub-sector companies listed on the Stock Exchange. Indonesia for the period 2014-2018. In conclusion, this study tries to examine how the influence of environmental disclosures on profitability in chemical industry sub-sector companies lised on the indonesian stock exchange in 2015-2019